IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM PENANGANAN BULLYING SISWA DI SEKOLAH DASAR - Richa Dwi Rahmawati (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2026)
This study aims to analyze the implementation of government policy in addressing student bullying in elementary schools based on the provisions of Permendikbudristek Nomor 46 Tahun 2023. The research employed a qualitative approach using a case study design conducted in an elementary school. The research participants included the principal, teachers, members of the Violence Prevention and Handling Team (TPPK), students, and parents. Data were collected through in-depth interviews, observation, and documentation study. Data analysis applied the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that structurally the school has implemented the policy through the establishment of the TPPK, the development of anti-bullying school regulations, and the dissemination of information to the school community. However, the effectiveness of implementation still faces challenges in terms of communication, limited trained human resources, and the lack of an optimal child-friendly reporting system. From the disposition perspective, there is a positive commitment from the school authorities, although certain forms of verbal bullying are still perceived as part of ordinary peer interaction. Overall, the policy implementation has been carried out administratively; however, strengthening technical, cultural, and evaluative aspects is necessary to create a safe and bullying-free school environment